(untitled) (Huellas, 2020)
The settlements of the West of La Pampa (Argentina) were historically linked to the presence of surface water resources. The Atuel River cutoff in 1947, and the subsequent irregular management of its waters, altered the way in which social groups inhabited the areas adjacent to its wetlands. The aim of this work is to contribute to understanding the changes experienced in the domestic peasant space and by the inhabitants of Paso Maroma and La Puntilla, changes that were caused by the effects of the conflict over the river. To achieve this, a qualitative methodology with data triangulation is applied, combined with written documents, cartographies and audiovisual material of in-depth interviews and field trips during 2018, 2019 and 2020. Firstly, the theoretical perspective is introduced, on which the case studies are analyzed. Then, a brief approach to the interprovincial conflict over the waters of the Atuel River is developed. Finally, a periodization is proposed to enable a diachronic tour of the puestos, the residential and productive peasant units with the largest presence in the area. Also, three modification processes of the domestic space that were motivated by the discontinuity of the river are identified.